Impact of Techno-Economic Breakthroughs in Photovoltaic LCOE on Green Hydrogen Costs - Hongyu ZHANG; Hongning XU; Dan LI; Junliang LI; Jie WANG; Deming WANG; Haichao ZHAO; Chongli ZHEN; Hong ZHAO (南方能源建设)
[Objective] International Hydrogen Council predicts that hydrogen energy will account for 18% of the total global end-use energy demand by 2050. In the technical path of green hydrogen preparation, the electricity cost of photovoltaic (PV) power generation is a key factor affecting the cost-effectiveness of hydrogen production by water electrolysis. [Method] Based on the solar resource data of typical regions in China, a levelized cost of energy (LCOE) calculation model was constructed to analyze the PV power generation costs at current and limit module costs, and quantify the marginal impact of photoelectric conversion efficiency improvement on LCOE. [Result] The results indicate that: with an annual effective power generation hours of 1200, LCOE for crystalline silicon photovoltaic cell system can be reduced to CNY 0.133 per kWh; However, the LCOE threshold of CNY 0.1 per kWh can be achieved for perovskite solar cell, crystalline silicon-perovskite tandem cell and dual tandem cell system with higher theoretical conversion efficiency when the annual power generation hours are 1008, 1092 and 864 respectively. When the LCOE for PV power generation is less than CNY 0.1 per kWh, the cost of hydrogen production by water electrolysis can be reduced to CNY 6.16 per kg. [Conclusion] With the reduction of module cost and the improvement of conversion efficiency, the LCOE for PV power generation in more than 90% of areas in China will have the potential to break through CNY 0.1/kWh. Within this cost range, green hydrogen will show a competitive advantage in production cost compared with traditional grey hydrogen and is expected to become the mainstream hydrogen source. This paper provides a quantitative basis for the industrialization of photovoltaic hydrogen production technology, and has an important reference value for optimizing the transformation path of energy structure and realizing the coordinated development of environmental benefits and economic benefits.